PERENCANAAN PENINGKATAN KINERJA: UPAYA MERANCANG DAN MERAIH KINERJA PRIMA - Yuliani, Febri (Universitas Riau, 2010)
Performance measurement is for assessing the success/failure/policy in accordance with the goalsand objectives that have been established in order to realize the mission and vision of the organization.Because, it is a matter of urgency to create a system that is able to measure performance and organizationalsuccess. To be able to answer the questions will be the level of success of an organization, then the entireorganization’s activities - not to the input (input) from the organization’s program but is concerned withoutput, processes, benefits and impact of organizational programs, of all things is important that thereperformance improvement planning.